(3ebOeGJ efJbi GdLeGfs - (3GdTGej GdYGedj, CHh efUhQ, GHf GdTgjO GdKGfj, GHf GdTgjO GdKGfj, GdMSf Hf Rjf GdOjf Hf Ydj GdTGej GdYGedj, J (B1011(3g` (B1602(3es ((3GdeTgO GdMSjfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3agPG GKfG YTQ ahGFO ddQLGd (B... (3GdaGFOI GdChdi(B: (3GUWdM GdeJCNQhf ef CUMGHfG Ydi JbSje GdNHQ HGYJHGQ GNJdGa CMhGd QhGJgs
(3BNQgG (B:s
(3BNQgG(B: (3YgPG GdTjN GdYXje GdTGf QLd (B... (3jfSH Edjg gPG GdJOdjS GdaGMT hGdUhGH MbbfGg hjbhj aj NGWQj EONGd GdMOjK GdeTJed Ydjg aj bSe GdMSf(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 192s
(3GdPQjYI, L (B22: 65s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs